ANALISIS PENGENDALIAN PERSEDIAAN SIMPLISIA PRODUK WEDANG UWUH (STUDI KASUS: CV SALAMA NUSANTARA) - Syifa Fauziah; Rika Nalinda; Siwitri Munambar (Universitas Sebelas Maret, 2024)
CV Salama Nusantara had not conducted calculations regarding inventory, and there were still raw materials accumulating in the warehouse (overstock), which could result in a reduction in profit and an increase in company expenses. Additionally, it was observed that there was a shortage of raw materials (stockout), leading to production interruptions and the company incurring higher costs for reordering in smaller quantities. This research aimed to understand the inventory system when using ABC and EOQ methods and the difference in Total Inventory Cost (TIC) values between the company’s and EOQ methods The study showed that the ABC method in the simplisia inventory system classified category A with 66.58% of the investment value for one type of simplisia, requiring greater control compared to categories B and C. The use of EOQ for ginger simplisia resulted in the highest EOQ value of 134.72 kg with an ordering frequency of 7 times. The comparison of Total Inventory Cost (TIC) for simplisia such as red ginger, cardamom, sappanwood, cinnamon, cloves, and nutmeg showed that the EOQ method resulted in a lower TIC compared to the company’s policy, with differences of Rp2,365, Rp12,973, Rp14,116, Rp65,494, Rp4,768, Rp16,055, and Rp66,048, respectively.